INVESTIGATION OF DNA THERMAL DENATURATION AT THE PRESENCE OF DIALKYLSULFOXIDES BY FLUORESCENCE SPECTROSCOPY (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The effect of dialkylsulfoxides (DASO) on the thermal denaturation of DNA was studied by fluoresence spectroscopy. As a fluorescence probe the ethidium bromide was used. It is revealed, that DASO shows expressed denaturing ability. In series of DMSO–DESO–DPSO with increasing of hydrocarbonic chain length of sulfoxides their denaturing ability increases, which is caused by the increase of direct hydrophobic interactions between DNA–DASO.
Keywords: thermal denaturation of DNA; dialkylsulfoxides; ethidium bromide; fluoresence spectroscopy